Blood Agar for the Isolation of M. tuberculosis in Comparison with LJ Medium and BACTEC MGIT 960 - Swetha Kamble; P Shashikala Reddy; Ch Navaneetha (Journal of Clinical and Diagnostic Research, 2018)
Introduction: The evolution of laboratory diagnostic methods of Tuberculosis (TB) over the past few years are designed to achieve more rapid, less expensive, and accurate results. However, acid-fast staining and culture for Mycobacteria remains the core of any diagnostic algorithm for TB. Aim: To assess 7% Sheep Blood Agar (BA) for the primary isolation of Mycobacterium tuberculosis in comparison with the Lowenstein-Jensen (LJ) medium and BACTEC Mycobacterial Growth Inhibitor Tube (MGIT) 960. Materials and Methods: This is a prospective study and was carried over a period of seven months in State TB Demonstration and Training Centre Intermediate Reference Laboratory (STDC-IRL), Erragadda Hyderabad, India from March 2014 to September 2014. About 100 clinically suspected TB cases (95 pulmonary and 5 extra pulmonary) were selected and respective samples were subjected to Ziehl-Neelsen (ZN) staining. Twenty one samples were positive and 79 were negative for Acid-Fast Bacilli (AFB). The samples were processed and inoculated on BA slants, LJ medium and BACTEC MGIT 960 (Becton, Dickinson and Company) bottles. The cultures were confirmed by ZN staining and speciated by biochemical reactions. Further, validation of growth on BA was identified by Genotype MTBDR plus (Hains Lifescience, Nehren, Germany) to confirm the growth of M. tuberculosis. Results: Approximately 100 samples inoculated, 40 {38 M. tuberculosis and 2 Non tuberculous mycobacteria (NTM)} were isolated on MGIT 960, 37 (34 M. tuberculosis and 3 NTM) on BA and 32 (30 M. tuberculosis and 2 NTM) on LJ medium. The average isolation time of BA LJ and BACTEC MGIT 960 TB was 13.2 days, 26 days and 11.8 days. Nearly 37 blood culture positive samples tested by Genotype MTBDR plus, 34 (91.89%) were confirmed as Mycobacterium Tuberculosis Complex (MTBC). The contamination rate was 2% on BA, 6% on LJ and 12% on BACTEC MGIT 960. Conclusion: Primary isolation of M. tuberculosis was achieved 8 to 18 days after inoculation of clinical samples on BA. It requires no specific equipment and therefore, BA can be prepared, utilised and also have the advantage of shorter turnaround time.